DESIGN AND RISK ANALYSIS OF SUBSEA PIPELINES DUE TO DROPPED AND DRAGGED SHIP ANCHORS BASED ON DNV-RP-F107 & DNV-RP-F111 STANDARD CODES - Dini Simanjorang, Rinto
The development of Indonesia's oil and gas production from offshore wells has become an attractive market for investment in the construction of subsea pipelines where subsea pipelines are used to deliver exploitation products from offshore platforms to processing and refining facilities. The installation of subsea pipelines has many safety requirements so planning is needed to ensure the pipelines are completely safe by considering the risk and frequency of failure. Subsea pipeline planning includes determining the wall thickness of the steel pipe, determining the on-bottom stability subsea pipeline, and assessing the risk of failure of the subsea pipeline. The steel pipe wall thickness analysis refers to the ASME B31.4 and API RP 1111 code standards, the on-bottom stability analysis refers to the DNV-RP-F109 code standard, and the subsea pipeline failure risk analysis refers to the DNV-RP-F107 & DNVRP- F109 code standards. The steel pipe wall thickness obtained based on the calculation results is 10.027 mm and 12.7 mm is selected. For the stability of the pipeline during operating conditions, the thickness of the concrete coating is 37.7 mm and 40 mm is selected. The subsea pipeline failure risk assessment produces a matrix that identifies whether the risk is in the tolerable area, or the area that requires additional control, and the intolerable area. The result of the assessment is that the risk of pipeline failure is at the ALARP and not tolerable level so that additional risk reduction controls are needed so that implementation can be considered feasible.